Cross-Sectional Study of Resilience, Positivity and Coping Strategies as Predictors of Engagement-Burnout in Undergraduate Students: Implications for Prevention and Treatment in Mental Well-Being - de la Fuente, Jesús; Santos, Flavia H.; Garzón-Umerenkova, Angélica; Fadda, Salvatore; Solinas, Giuliana; Pignata, Silvia (Frontiers in Psychiatry, 2021)
In a population of young adults, this study analyzes possible linear relations of resilience and positivity to coping strategies and engagement-burnout. The aim was to establish a model with linear, associative, and predictive relations, with which to identify needs and make proposals for therapeutic intervention in different student profiles. A population of 1126 undergraduate students with different student profiles gave their informed, written consent, and completed validated questionnaires (CD-RISC Scale; Positivity; Coping Strategies of Stress; Engagement, and Burnout). An ex post facto design involved bivariate association analyses, multiple regression and structural predictions (SEM). The results offered evidence of associations and predictive relationships between resilience factors, positivity, coping strategies and engagement-burnout. The factors of resilience and positivity had significant differential associations (positive and negative) with factors of coping strategies. Their negative relationship to burnout factors, and positive relation to engagement factors, is especially important. Results of structural analysis (SEM) showed an acceptable model of relationships between variables. We conclude with practical implications for therapeutic intervention: (1) the proactive factors of resilience reflect a perception of self-efficacy and the ability to change adaptively; (2) the reactive factors of resilience are usually associated with withstanding experiences of change, uncertainty or trauma.